Determinación cuantitativa de CBD presente en la planta de cannabis, en las especies Hard Diesel (Sativa) y Black Domina (Indica) a partir de extracción química con etanol. (2021)
The medical cannabis industry in Colombia is an alternative for economic growth with considerable potential and which is also little explored for legal and investment reasons, but above all for cultural reasons. It is known that scientifically a great development has emerged in the field of medicine from cannabis in first world countries, a clear example of this is the United States, which has also focused its technology on optimizing and improving cannabinoid extraction methods and the cultivation of different species of cannabis. However, a direct comparative study on the amount of CBD present between Hard Diesel and Black Domina species as potential sources and possible raw materials within the industry is not specifically known.